Supply chain modelling frameworks for forest products industry: a systematic literature review. Issue 1 (2nd January 2016) - Vahid, Saba; Lehoux, Nadia; de Santa-Eulalia, Luis A.; D'Amours, Sophie; Frayret, Jean-Marc; Venkatadri, Uday
ABSTRACT: Considering the economic importance of forest products industries in Canada, there has been an increasing interest in studying the operations and interactions of all the relevant entities involved in its supply chain (SC). The forest products industry has a set of specific SC characteristics to meet the needs of its final consumers. While a growing number of mathematical and simulation models are being presented for the SC in this sector, an integrated formal structure is evidently required for guiding the development of and evaluating these models. Therefore, in this research, we systematically review and identify existing frameworks for modelling SCs with the interest of highlighting the ones relevant to the forest products SCs. While we find no framework specific to the forest products industry, we identify a number of existing frameworks that could be customized to represent the industry's SC.